PSYCHOLOGICAL IMPACT OF SOCIAL NETWORKS ON PERSONAL BEHAVIOR (American Journal of Research in Humanities and Social Sciences, 2024)
This article describes the concepts that influence the personality and behavior, the changes that occur in people in the current globalization period, the psychological developments, the study of the causes of the difficulties that arise, the personality of an individual as a result of certain factors. aimed at studying the mechanisms that cause change. The main topic is ways to create the right social environment during the period of a number of changes that occur in adolescents. In addition, the article also talks about preventing pedagogical and psychological problems that arise in the youth of individuals.